Metabolomic and transcriptomic analyses of rice plant interaction with invasive weed Leptochloa chinensis - Zhang, Liang; Chen, Ke; Li, Tianrui; Yuan, Shuren; Li, Chenyang; Bai, Lianyang; Wang, Lifeng (Frontiers in Plant Science, 2023)
Leptochloa chinensis is an annual weed in paddy fields, which can engage in competition with rice, leading to a severe yield reduction. However, the underlying mechanism governing this interaction remain unknown. In this study, we investigated the mutual inhibition between rice and the weed under mono-culture and co-culture conditions. We found that the root exudates of both species played essential roles in mediating the mutual inhibition. Further metabolomic analysis identified a significant number of differential metabolites. These metabolites were predominantly enriched in the phenylpropanoid and flavonoid biosynthesis pathways in weed and rice.Transcriptomic analysis revealed that the differentially expressed genes responding to the interaction were also enriched in these pathways. Phenylpropanoid and flavonoid biosynthesis pathways are associated with allelopathy, indicating their pivotal role in the response of rice-weed mutual inhibition. Our findings shed light on the conserved molecular responses of rice and L. chinensis during their interaction, provide evidence to dissect the mechanisms underlying the allelopathic interaction and offer potential strategies for weed management in rice paddies.